Dictionary of Sociology / Third Edition - Abercrombie Nicholas; Hill Stephen; Turner Bryan S (Penguin Books, 1994)
An invaluable and comprehensive reference work designed to appeal to students from school to university level. Preface, How to Use this Dictionary, Dictionary of Sociology, Bibliography.